2017
DOI: 10.1590/0100-29452017171
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT OF Tetranychus urticae KOCH (ACARI: TETRANYCHIDAE) IN DIFFERENT STRAWBERRY CULTIVARS

Abstract: -two-spotted spider mite, Tetranychus urticae Koch, is considered the main pest in strawberry crop. The control of this species is hampered by the low efficiency of products currently used, occurrence of populations resistant to acaricides and high reproductive potential of this pest. this leads to the use of pesticides and increased agrochemical residues in fruits. the use of resistant cultivars is considered the ideal control method because they maintain mite populations below levels of economic damage, mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
(14 reference statements)
1
9
1
4
Order By: Relevance
“…In the present work, the density of trichomes in 'Camarosa' was higher than that observed in 'Albion', and it can be inferred that this characteristic can be highly influenced by the environment. However, Karlec et al (2017) reported that the Camarosa cultivar may exhibit antibiosis-type resistance to the two-spotted mite, whose preferences regarding feeding, development and oviposition differed from the results obtained in this research.…”
Section: Identification and Quantification Of Trichomescontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present work, the density of trichomes in 'Camarosa' was higher than that observed in 'Albion', and it can be inferred that this characteristic can be highly influenced by the environment. However, Karlec et al (2017) reported that the Camarosa cultivar may exhibit antibiosis-type resistance to the two-spotted mite, whose preferences regarding feeding, development and oviposition differed from the results obtained in this research.…”
Section: Identification and Quantification Of Trichomescontrasting
confidence: 99%
“…The obtained results indicated that there was an influence of the preselected hybrids and cultivars on the behavior of the spider mites, allowing us to verify the existence of superior genotypes, such as the hybrids RVDA#16 and # RVCS#44 and the cultivar Camino Real, which showed greater resistance. The results indicated that spider mite resistance was related to the mechanisms of the antibiosis types and not preference (Karlec et al, 2017).…”
Section: Identification and Quantification Of Trichomesmentioning
confidence: 91%
See 1 more Smart Citation
“…This crop is mainly cultivated by peasant farmers, with little technical and financial assistance (Redagrícola, 2017). The two-spotted spider mite (T. urticae) is a polyphagous pest that affects more than 1,000 vegetable species of 140 different families (Grbić et al, 2011) and is regarded as the most important pest of strawberry (González-Domínguez et al, 2015;Karlec et al, 2017), causing the death of the plant (Hoy, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, these areas are necrotic, with perforations in the leaves [2] . Under severe infestations, these can cause early defoliation, affecting productivity [3] . The occurrence of this mite is reported in regions of hot and humid climate, mainly during the hottest periods of the year [4] .…”
Section: Introductionmentioning
confidence: 99%